Project Management in Cross-Sector Partnership: A Systematic Literature Review - Maja JOKIEL; Grzegorz JOKIEL; Robert BOBKIER; Arkadiusz BABCZUK (Communications of International Proceedings, 2024)
This paper aims to synthesize knowledge about project management (PM) in cross-sector partnerships (CSP) from three perspectives: project methodology (methodology), project leadership (PL), and project team building (TB). Significant gaps in the literature on "universal" descriptions of the phenomenon of project management in cross-sector partnerships are noted. This indicates the need for a comprehensive and well-established conceptual framework or models to explain project management specifics in CSP. The research gap is related to the lack of a comprehensive, unified theoretical and practical approach to project management in cross-sector partnerships that considers the specificities of this type of cooperation and explains the key factors that affect the effectiveness of project implementation (Murphy et al., 2023; Murphy, D.F, 2023). A bibliometric analysis of articles indexed in the Scopus database was carried out (as a result, 58 articles were identified). After analyzing abstracts and a manual in-depth review, the final sample comprised 24 documents. In their descriptions, the authors focused primarily on presenting PM in CSP in the objective aspect, rarely focusing on the subjectivity of the PM in the CSP aspect. This article identified the following conclusions. All authors in the articles analyzed agree that there are no 'universal' descriptions of the PM in the CSP phenomenon. Another conclusion is that there is a relatively high asymmetry of knowledge, mainly due to the power and ownership of the funds that finance implementation The most common theories cited by the authors are: resource-based view theory, agency theory, resource-based theory, institutional theory, affect theory and value creation theory. It is essential to continuously monitor scientific developments in this field, as this may facilitate the description of the CSP phenomenon.
Keywords: cross-sector partnership; project management; types of cross-sector partnership.